Effect Carrier Materials of Bradyrhizobium sp. strain PZS_A08 on Growth of Indigofera zollingeriana - Wilhelmus Terang Arga Sanjaya; Sari Yulia Kartika; Desak Ketut Tristiana Sukmadewi; Rahayu Widyastuti; Iswandi Anas (JOURNAL OF TROPICAL SOILS, 2021)
Sustainable forage production is needed to meet animal feed needs as the livestock industry increases. The purpose of this study is to evaluate the effect of liquid and solid carrier material on the effectiveness and infectivity of Bradyrhizobium sp. strain PZS_A08 on the growth of Indigofera zollingeriana (I. zollingeriana). The two carrier materials used were zeolite (solid) and molasses (liquid). This study used two carrier materials consisting of zeolite (solid) and molasses (liquid). The five treatments given were P0 (50% NPK), P1 (50% NPK+liquid biofertilizer), P2 (50% NPK+sterile liquid biofertilizer), P3 (50% NPK+solid biofertilizer), P4 (50 % NPK+sterile solid biofertilizer), P5 (100% NPK). Observations were made on the plant's height, number of leaves, number of nodules, upperparts and root wet biomass, root and upper parts dry biomass, root length, and microbial population). The use of liquid and solid carrier materials effectively affected the effectiveness and infectivity of Bradyrhizobium sp. strain PZS_A08 on  I. zollingeriana. Inoculants Bradyrhizobium sp. strain PZS_A08 significantly increased plants' growth and reduced the use of 50% NPK fertilizer. Cold storage temperature (5ºC) effectively maintained Bradyrhizobium sp. strain PZS_A08 on liquid and solid carriers, while solid carriers showed better effectiveness at room temperature storage (30oC). Through this research, solid carriers such as zeolite are recommended as carriers for Bradyrhizobium sp. filter PZS_A08.